Mechanical Behaviour of Glass Fibre-Reinforced Polymer/Polyvinyl Chloride Foam Cored Sandwich Structures - Edwin Cheruiyot Kosgey; Krishnan Kanny; Festus Maina Mwangi (Advances in Materials Science and Engineering)
This study focuses on the fabrication and analysis of the mechanical behaviour of unidirectional (UD) glass fibre-reinforced polymer (GFRP) facesheet and polyvinyl chloride (PVC) foam core sandwich structures fabricated by a vacuum-assisted resin infusion method (VARIM). These sandwich structures are commonly used in marine and wind turbine blade applications. To date, relatively little knowledge about the functional behaviour of UD GFRP compared to composites reinforced with bidirectional mats is available for day-to-day applications. The effects of the facesheet orientation, facesheet thickness, and core thickness on the mechanical behaviour of the specimens were examined. The UD fibres were oriented in cross-ply (0/90), angle-ply (+45/−45), and quasi-isotropic orientations. Various mechanical properties such as tensile, flexural, flatwise compression, and edgewise compression tests were examined. Characterization of the tensile properties of the facesheet showed that the cross-ply orientation had a higher strength than the angle-ply and quasi-isotropic orientations. The flexural load-carrying capacity of the cross-ply facesheet orientation was superior to the other orientations. The increase in the core thickness changed the flexural failure mode from face yield and core shear to core indentation. Flatwise compression (FWC) was tested to determine the core characteristics of the sandwich structure, and the peak loads of 4.90, 1.81, and 3.90 kN were obtained for 10-, 15-, and 20 mm core thicknesses, respectively. Edgewise compression (EWC) exhibited stable end crushing for thinner facesheet, whereas thicker facesheet showed core crushing and buckling. When the facesheet thickness was increased from 1.5 mm to 3 mm in the EWC, the buckling load increase ranged from 2.53% to 44.83% for core thicknesses 10-, 15-, and 20 mm, respectively.